Achados clínicos de afecções orais em bugios ruivos (Alouatta guariba clamitans) (Cabrera, 1940) - Dias Neto, Ramiro das Neves [UNESP] (2014)
The aim of this study was to investigate dental disorders of Brown howler monkeys (Alouatta guariba clamitans) maintained in captivity. The hypothesis is that the identification and diagnosis of the lesions may contribute to control and prevention. Sixteen intact red howler monkeys (Alouatta guariba clamitans), 8 females and 8 males, weighing from 3.9 to 6.8 kg were studied. Under general anesthesia, the teeth were evaluated by visual inspection, probing, palpation, and intraoral radiographic exam. The findings were registered on dental chart specific for primates. From the 16 monkeys evaluated in the present study, 88% (n=14) had some type of dental disorder. The lesions observed were dental calculus (88%), dental wear (81%), missing tooth (38%), gingivitis (19%), gingival recession (6%), dental fracture (19%), pulp exposition (19%), and dental staining (25%). Alouatta guariba clamitans maintained in captivity have high rate of dental problems